Le sida, l’homophobie et le discours biomédical : une épidémie de signification [1987] - Paula Treichler (Genre, Sexualité et Société)
This article examines the AIDS discourse that emerged in the United States in the early 1980s. It analyzes how the press, but also medicine (including public health and medical research), carry along discriminatory and often homophobic preconceptions while developing their own stories and conceptual frameworks of the epidemic. It stresses the fact that science is not immune to prejudices against stigmatized groups. Following the tradition of « science studies », it sheds light upon the wavering of science and on the conflicts of interpretation that the most affected communities have raised for a better match between the research and their needs.